Sin dar el brazo a torcer: cláusulas shotgun como mecanismo de solución eficiente ante un bloqueo societario - Monsante Moy, Isabella (2023)
The corporate deadlock is not a situation that remains remote at all in Peruvian’s corporate practice. Despite that fact, Peruvian organizational law was proven to be insufficient to solve this problem. With that scenario, Peruvian corporate lawyers were in the need of seeking contractual solutions, importing Common Law conventional solutions; namely shotgun provisions that are the clauses mostly included in shareholders’ agreements to solve a possible corporate deadlock.This article aims to introduce the shotgun provisions as the most efficient solution before a corporate deadlock situation presented in a sociedad anónima cerrada and sociedad anónima (Peruvian regulated legal entities for private corporations) with shareholders who share equal participation in the Capital. The different possible solutions that the Peruvian General Corporation Law offers will be addressed and the viability of their application in corporate deadlocks will also be analyzed. It will be concluded that the most efficient solution to a corporate deadlock results in the use of the shotgun provisions contained in the shareholders’ agreement within a transaction in which a significant percentage of shares is acquired.